Determination of effective miRNAs in wound healing in an experimental Rat Model - Coskunpinar, E; Arkan, H; Dedeoglu, B G; Aksoz, I; Polat, E; Araz, T; Aydos, A; Oztemur, Y; Akbas, F; Onaran, I (Cellular and Molecular Biology, 2015)
The larvae of Lucilia sericata have been used for centuries as medicinal maggots in the healing of wounds. The present study aimed to screen potential microRNAs related to ES-induced wound healing in rat skin wounds and to investigate the potential mechanisms contributing to accelerated wound healing. Healthy, male, 12 weeks old Wistar albino rats weighing 250–300 g were supplied by the Animal Experimental Center. All animal studies were performed in accordance with the NIH Guide for the Care and Use of Laboratory Animals. Wistar albino rats were treated by ES after post wounding and the differentially expressed miRNAs in wound biopsies were screened by microarray analysis at the end of treatments for 4,7 and 10 days. In addition, bioinformatics approaches were used to identify the potential target genes of differentially expressed miRNAs and the functions of their target genes. We found a significant up-regulation of rno-miR-99a* and rno-mir-877 in response to ES treatment. Further investigation of rno-miR-99a* and rno-mir-877 and their target genes (TGFa, TNF, TAGLN, MAPK1, MMP-9) implicated in present study could provide new insight for an understanding lead to the development of new treatment strategies. The identified miRNAs can be new biomarkers for ES- induced wound healing.